Antarctic Snow Radar-Derived Relative Accumulation Product - Dattler, Marissa; Lenaerts, Jan; Medley, Brooke (Zenodo, 2019)
Small-scale Antarctic accumulation rates relative to MERRA-2 precipitation-evaporation as derived from NASA Operation IceBridge snow radar.